Honderd Jaar Hervormde Teologie - Dreyer, Wim A. (HTS teologiese studies, 2017)
The Faculty of Theology of the University of Pretoria is celebrating its centenary during 2017. Since its inception in 1917, the Nederduitsch Hervormde Kerk van Afrika (by agreement) appointed lecturers in the Faculty and more than a thousand ministers of the Hervormde Kerk received their theological education at the University of Pretoria. As such, the centenary of the Faculty is also a celebration of hundred years of ‘Hervormde theology’. This contribution reflects on two publications (by M.J. Goddefroy and P.J .Muller, respectively) which appeared in 1890 and 1908, firstly to give an overview of the prehistory of the establishment of the Faculty of Theology and secondly to illustrate the diverse origins and nature of Hervormde theology as reflected in the publications of Goddefroy and Muller.